Organizational Citizenship Behavior: The Role of Job Fit, Job satisfaction, and Transformational leadership - Nikmah, Ulfatun; Kurniawan, Ignatius Soni; Kusuma, Nala Tri (Jurnal Ilmu Manajemen Profitability, 2025)
This study investigates the influence of person–job fit, job satisfaction, and transformational leadership on organizational citizenship behavior (OCB) among employees of the Cultural Service of the Yogyakarta Special Region. OCB represents discretionary employee behavior that enhances organizational functioning but is not explicitly required in formal job descriptions. A quantitative research design was employed, using a census method to collect data from 100 employees through structured questionnaires. The research instruments were adapted from validated scales, and the data were analyzed using multiple linear regression with SPSS version 23. The findings reveal that person–job fit exerts a significant positive effect on OCB, indicating that alignment between employees’ competencies and job demands encourages greater voluntary contributions. Job satisfaction also demonstrates a significant influence, suggesting that satisfied employees are more likely to engage in behaviors that support organizational effectiveness. Moreover, transformational leadership is found to have a strong positive effect on OCB, underscoring the role of inspirational and visionary leadership in motivating employees to perform beyond formal requirements. Collectively, the three predictors explain 94.5% of the variance in OCB, reflecting their substantial contribution to discretionary work behaviors. These results highlight the importance of enhancing job–person alignment, fostering job satisfaction, and strengthening transformational leadership to cultivate OCB in public sector organizations. The study contributes to the literature on organizational behavior and offers practical implications for improving employee performance through human resource management strategies.